Correlation of Family Support on Physical Rehabilitation Compliance in Stroke Patients - Adhisty Fachrine Ayu Saqina; Dian Hudiyawati (Indonesian Journal of Global Health Research, 2024)
As a result of suffering from stroke disease, stroke patients experience disability, lose the ability to live independently, and affect their quality of life and daily activities. Rehabilitation programs are used to improve patient function and overcome the impact of stroke. Family support plays a very important role in the recovery process and rehabilitation compliance of stroke patients. This study aims to determine the correlation of family support to rehabilitation compliance in stroke patients at Ir Soekarno Sukoharjo Hospital. The type of research used in this study is quantitative research. The study sample totalled 73 patients, obtained by using the purposive sampling technique and the Slovin formula. The inclusion criteria for this study were stroke patients undergoing physical rehabilitation at Ir. Soekarno Sukoharjo Hospital, patients without disorientation in time, space, or people, and patients who had undergone physical rehabilitation for 2-3 months and were willing to become respondents. The exclusion criteria for this study were patients who had mental disorders and patients who had congenital physical disabilities. The questionnaires used in this study were the family support questionnaire and the modified Morinsky Medication Adherence Scale (MMAS) questionnaire. Data analysis will be displayed in the form of distribution tables, frequencies, and percentages so that it is easily understood by the reader. The results of this study showed that the majority of respondents had high family support with high rehabilitation compliance as many as 30 people (41.1%), respondents had moderate family support with high rehabilitation compliance as many as 14 people (19.2%), respondents had moderate family support with moderate rehabilitation compliance as many as 12 people (16.4%), respondents had high family support with moderate rehabilitation compliance as many as 1 person (1.4%), and respondents with moderate family support with high rehabilitation compliance as many as 16 people (21.9%). The results of the Spearman Test between family support and physical rehabilitation compliance obtained a P-value of 0.001 with a correlation coefficient value indicate that there is a strong relationship between family support and physical rehabilitation compliance in stroke patients at Ir. Soekarno Sukoharjo Hospital.